Pengaruh Rebusan Daun Jambu Biji Terhadap Indeks Plak pada Siswa SMAN 1 Juli Kabupaten Bireuen - Nurul Aqna (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Background: Oral health problems remain a major health concern among adolescents. Dental plaque accumulation is the primary cause of dental caries and periodontal disease. The use of chemical mouthwashes, such as chlorhexidine, is associated with several side effects, highlighting the need for alternative herbal mouthwashes. Guava leaves (Psidium guajava L.) contain guaijaverin and quercetin, which possess antibacterial properties and have the potential to inhibit dental plaque formation. Objective: To determine the effect of rinsing with boiled guava leaf water on plaque index in students of SMAN 1 Juli, Bireuen Regency. Methods: This study used a quasi-experimental design with a pretest-posttest design and a control group. The study population was 352 students, and a sample of 78 students was selected using proportional sampling. The sample was divided into two groups: 39 students in the treatment group who rinsed with boiled guava leaf water and 39 students in the control group who rinsed with mineral water. Plaque index measurements were performed using the PHP Index before and after treatment. Data were analyzed using the Wilcoxon Signed Rank Test.  Results: The study showed a significant reduction in plaque index in the group that gargled with guava leaf decoction, with a p-value of 0.000 (p<0.05). Meanwhile, the group that gargled with mineral water showed no significant change, with a p-value of 0.520 (p>0.05). Conclusion: Guava leaf decoction reduced plaque index in students at SMAN 1 Juli, Bireuen Regency. Recommendation: Guava leaf decoction can be used as an alternative herbal mouthwash to help maintain dental and oral hygiene. Further research is recommended with a larger sample size and a longer intervention period to achieve more optimal results.